ORIENTALISM AND ISLAM: A BIBLIOMETRIC ANALYSIS - Muhammad, Fatimah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study explores the intellectual landscape of research on “Orientalism and Islam” through a bibliometric analysis, aiming to uncover patterns, trends, and emerging themes that have shaped scholarly engagement with this topic. Despite the longstanding significance of Orientalist discourse in shaping global perceptions of Islam, a comprehensive mapping of its academic treatment has remained limited. To address this gap, data were collected from the Scopus database using advanced searching techniques, yielding a total of 2,183 documents. The dataset was refined and harmonized using OpenRefine to ensure consistency and accuracy in author names, keywords, and institutional affiliations. Statistical distributions and graph-based analyses were then generated using the Scopus Analyzer, while VOSviewer software was employed to visualize co-authorship networks, keyword co-occurrence, and country-level collaboration patterns. The findings reveal the United States and the United Kingdom as the leading contributors, followed by growing participation from Indonesia, Malaysia, Turkey, and Iran, indicating a diversification of research voices beyond traditional Western centers. Keyword co-occurrence analysis identified six major clusters, highlighting dominant themes such as Orientalist discourse, Islamic identity, postcolonialism, political Islam, Islamophobia, and intercultural dialogue. These clusters suggest a dynamic interplay between historical critiques of Orientalism and contemporary issues related to Islam and Muslim societies. Furthermore, citation analysis demonstrated the prominence of interdisciplinary contributions spanning religious studies, sociology, political science, and cultural studies, underscoring the cross-cutting nature of the discourse. In conclusion, this bibliometric mapping provides a holistic overview of the field, contributes to a deeper understanding of global research dynamics on Orientalism and Islam, and offers valuable insights for future scholarship seeking to bridge critical theory with contemporary socio-political realities.